Erotomanic delirium, a case report in a General Hospital of Lima. - Alza-Zegarra, Elena (2022)
Among the so-called delusional disorders, the erotomanic subtype is characterized by, the delusional belief that a person, usually of higher social and intellectual status, is in love with the patient. The case of a young man whose clinical picture consists in his romantic relationship with an Argentinian singer who fell in love with him through the screen and communicates by telepathic connections, is presented. Erotomanic delirium is an uncommon and poorly documented pathology, particularly in mental health areas of general hospitals. It is important to remain awareness of cases like this in order to provide reliable information and make it possible a timely diagnosis and treatment.